EXPRESSIVE SPEECH ACTS IN LITTLE WOMEN MOVIE - Nityasa, Sekar Arum; Masykuroh, Qanitah (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
This research investigates the types and strategies of expressive speech acts uttered by the female main character in the 2019 movie Little Women. Employing a qualitative content analysis design, the study focuses on the female protagonist's utterances that contain expressive speech acts. The data for this research are drawn from the movie transcript of Little Women, directed by Greta Gerwig. Documentation is used to collect the data, which are then analyzed using Searle’s (1979) theory for types of expressive speech acts and Yule’s (1996) theory for strategies of expressive speech acts. The analysis reveals 35 instances of expressive speech acts, including nine apologizing, three congratulating, eight deploring, seven expressing gratitude, two welcoming, and six wishing. Additionally, the research identifies 18 direct speech utterances and 17 indirect speech utterances. This study highlights how the types and strategies of expressive speech acts contribute to the characterization of the main female character in the movie.